Understanding solastalgia from a decolonised, Indigenist lens: a scoping review - Upward, Kisani; Usher, Kim; Saunders, Vicki; Maple, Myfanwy (Frontiers in Public Health, 2024)
The objective of this review is to use a decolonised, Indigenist lens to understand the definition of solastalgia from an Aboriginal perspective, as a potential emotional response experienced by Aboriginal communities impacted by increasingly frequent natural disasters, such as bushfires. Initial search results revealed a lack of literature referencing solastalgia in an Aboriginal-specific context. Indigenist research methodologies such as Heuristic inquiry and Aboriginal Participatory Action Research (APAR) contributed to the identification of alternative terminologies, which led to the majority of the included publications referring to solastalgia-related concepts, with one included publication mentioning solastalgia specifically. These methods were consequently used to synthesize data, confirm results and contribute to final discussions. Lastly, our results determined that at this stage there is insufficient evidence to conclusively suggest that Aboriginal Peoples in a general sense, experience solastalgia. Acknowledging the ethical dilemma and potential harm of generalising personal philosophies and experiences based on Culture. Thereby, signify the need for further research in this space and in particular, from a decolonised, Indigenist perspective. Preface In the context of this review, we as co-authors are mindful of and respect the tensions or politics associated with proclaiming or discussing the identities of Australia's First Peoples. Therefore, in the context of this review, the often preferred term Aboriginal refers to the traditional owners of Australia. Where possible, traditional place/tribe names are written to acknowledge the ownership and origins of the information referenced within this review. Furthermore, we wish to acknowledge the storeys and traditional knowledge shared by the authors of the studies referenced within this review. These words of Country and Kin have contributed to the development and conceptualisation of this literature review, and we wish to pay our respects and appreciation.